Preparation and investigation indium tin oxide for transparent electrode of MS Schottky photodiode - N Sangwaranatee; I Srithanachai (My University, 2022)
Abstract In this paper investigation photocurrent of MS Schottky photodiode by using transparent electrode. The transparent material use in this investigation is indium tin oxide (ITO). Transparent electrode can help to get more photocurrent under contact due to light can penetrate though into depletion region then generate photocurrent. ITO will prepare by RF sputtering technique and investigate material characteristics such as electrical and optical properties. Optimize ITO properties after various thickness by growth sputter time show high transparent around 91.2% with low resistance 3.4x10 -3 ohm-cm. Build in voltage of device show 0.3V by same with metal contact and current under light exposure show around 1.5mA at 25,000 lux with bias -5V.
Keywords: Photocurrent; Indium tin oxide; Photodiode; Tin oxide; Thin-Film Transistor Technologies